The Role of PPARs in Disease - Wagner, Nicole; Wagner, Kay-Dietrich (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint combines recent original manuscripts and reviews covering the multiple functions of peroxisome proliferator-activated receptors in physiology and pathophysiology. Potential applications and limitations of PPAR agonists and antagonists are discussed. All original contributions were published in Cells.